2016
DOI: 10.1177/1866802x1600800204
|View full text |Cite
|
Sign up to set email alerts
|

Censoring the Press: A Barometer of Government Tolerance for Anti-regime Dissent under Authoritarian Rule

Abstract: This paper proposes that dissident leaders aiming to build mass opposition movements follow the mainstream press to help them gauge government tolerance for anti-government mass actions in repressive authoritarian regimes. Under conditions of censorship, media–state interactions serve as a barometer of the government's disposition toward and capacity to impede public displays of dissent. Observing trends in coverage and the government's reaction to this coverage helps activist leaders assess when it should be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Several formal models suggest that media independence facilitates dissent by spreading information, although it may also increase the risk of repression (e.g., Kim, Whitten-Woodring, and James 2015; Whitten-Woodring and James 2012). Stein (2016a) shows how the Folha de Sao Paulo newspaper in Brazil provided information that helped opposition actors mobilize against the military regime. These studies offer many valuable insights, but comparative empirical research on the mass media–dissent nexus remains scant.…”
Section: Information and Collective Action In Autocraciesmentioning
confidence: 99%
“…Several formal models suggest that media independence facilitates dissent by spreading information, although it may also increase the risk of repression (e.g., Kim, Whitten-Woodring, and James 2015; Whitten-Woodring and James 2012). Stein (2016a) shows how the Folha de Sao Paulo newspaper in Brazil provided information that helped opposition actors mobilize against the military regime. These studies offer many valuable insights, but comparative empirical research on the mass media–dissent nexus remains scant.…”
Section: Information and Collective Action In Autocraciesmentioning
confidence: 99%
“…One explanation is that most East Germans did not use West German media for political purposes. Meanwhile, the case study from Brazil unveils that when the national news media touches upon taboo stories, implying a regime's tendency to liberate the country, massive political oppositions are more likely to appear (Stein, ). Another study indicates that media watchdogging confirmed Tunisians’ perception about a weak government, triggering nationwide protests (Kim, Whitten‐Woodring, and James, ).…”
Section: Media and Protest In Advanced Democracies And Beyondmentioning
confidence: 99%
“…Ten years before the ending of military rule in Brazil, taboo topics began to surface in national newspapers. Subsequently, civil society was rejuvenated and mass protests followed, ultimately leading to political liberalization (Stein, ). In Taiwan, mass student movements occurred after the ruling party Kuomintang lifted the ban on newspaper publications in the late 1980s (Chen, ).…”
mentioning
confidence: 99%
“…Although most people agree that the growth of ICTs has greatly influenced society and politics, little agreement exists on the mechanism by which ICT diffusion effects change or the nature of such change. First, as more people gain access to ICTs, they improve their access to information—even where censored—which allows them to better evaluate the political regime that rules over them (Stein, ). As the number of sources increases and the news cycle develops instantaneously, it becomes increasingly difficult for governments to keep pace with monitoring and censoring alternative information sources.…”
Section: Dictators’ Digital Dilemma: To Inhibit or To Invest In Ict Imentioning
confidence: 99%